A modified ant colony optimization algorithm modeled on tabu-search methods - Ho, S. L.; Yang, S. Y.; Ni, G. Z.; Machado, J. M. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
An earlier model underlying the foraging strategy of a pachycodyla apicalis ant is modified. The proposed algorithm incorporates key features of the tabu-search method in the development of a relatively simple but robust global ant colony optimization algorithm. Numerical results are reported to validate and demonstrate the feasibility and effectiveness of the proposed algorithm in solving electromagnetic (EM) design problems.
Keywords: ant colony optimization (ACO); design optimization; foraging behavior; tabu search method